2019
DOI: 10.1021/acs.jnatprod.8b00856
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Potential of Saponins from Aster tataricus via NF-κB/MAPK Activation

Abstract: Four new aster saponins (1–4) together with five known analogues (5–9) were isolated from Aster tataricus. The chemical structures of 1–4 were elucidated based on spectrometric and spectroscopic analysis and comparison with reported data. The potential anti-inflammatory activities of aster saponins 1–9 were evaluated subsequently by measuring lipopolysaccharide (LPS)-enhanced nitric oxide (NO) formation in murine macrophages. Among these, aster saponin B (6) exhibited the most potent inhibitory activity (IC50:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…During the process of pulmonary diseases, inflammatory reaction plays an important role (Welbourn and Young, 1992; Ghio and Devlin, 2001; Ricard et al, 2001; Peng et al, 2004; Menezes et al, 2005). Many preliminary studies confirmed the anti-inflammatory and immune-regulatory effects of natural products, while several data showed a decreased effect of their metabolites on cytokines for inflammation, such as IL-1, IL-6, and TNF-α (Teng et al, 2016, Teng et al, 2017; Chen et al, 2018, Chen et al, 2019; Gupta et al, 2019; Magalhães et al, 2019; Saudagar and Saokar, 2019; Su et al, 2019; Zhang et al, 2019). Hence, it arouses our interest that whether MXD, a famous traditional Chinese medicine formula widely used in respiratory diseases, can alleviate PM2.5 induced lung injury.…”
Section: Discussionmentioning
confidence: 93%
“…During the process of pulmonary diseases, inflammatory reaction plays an important role (Welbourn and Young, 1992; Ghio and Devlin, 2001; Ricard et al, 2001; Peng et al, 2004; Menezes et al, 2005). Many preliminary studies confirmed the anti-inflammatory and immune-regulatory effects of natural products, while several data showed a decreased effect of their metabolites on cytokines for inflammation, such as IL-1, IL-6, and TNF-α (Teng et al, 2016, Teng et al, 2017; Chen et al, 2018, Chen et al, 2019; Gupta et al, 2019; Magalhães et al, 2019; Saudagar and Saokar, 2019; Su et al, 2019; Zhang et al, 2019). Hence, it arouses our interest that whether MXD, a famous traditional Chinese medicine formula widely used in respiratory diseases, can alleviate PM2.5 induced lung injury.…”
Section: Discussionmentioning
confidence: 93%
“…RAW 264.7 (ATCC TIB-71) cells were cultured in Dulbecco’s modified Eagle medium (DMEM) and NO assay was carried out for measurements of NO release using previously reported method [46]. Briefly, RAW 264.7 cells were plated at 1 × 10 5 cell density in a 96-well microplate and cultured for 24 h. Compounds ( 1 – 22 ) were pretreated with increasing dose concentrations (0.5, 1, 5, 10, 25, 50, and 100 μM), and then stimulated with LPS (1 μg/mL, Sigma–Aldrich, St. Louis, MO, USA) for 18 h. The mixture of cell supernatant (100 μL) and Griess reagent [1% sulfanilamide + 0.1% N -(1-naphthyl)ethylenediamine (Sigma–Aldrich)] in 5% phosphoric acid was recorded at 550 nm using a microplate reader (Varioskan LUX, Thermo Fisher Scientific Inc., Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…5B) 6F), which was restored in ATE (100 mg/kg and 500 mg/kg)-treated groups significantly (p<0.05). Traditionally, A. tataricus is used for medicinal and several reports have indicated the presence of numerous bioactive constituents including dietary flavonoids, triterpenes, saponins and specific constituents such as epifriedelinol, caffeoylquinic acids, shionone and aster peptides shionone, epifriedelinol, quercetin, kaempferol, scopoletin, emodin, aurantiamide acetate and 1,7-dihydroxy-6-methyl-anthraquinone [49][50][51][52] . Some of these compounds, such as quercetin, saponins, kaempferol, epifriedelinol, caffeoylquinic acids possess strong antioxidant, antiinflammatory and hepatoprotective properties including antifibrotic effects [53][54][55][56] .…”
Section: Fig 1: Effect Of Ate In Cell Viability Assay On Chang Livermentioning
confidence: 99%
“…A. tataricus was also reported to have antioxidant activity and reduce the levels of alanine aminotransferase (ALS), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) in hepatotoxic effect induced by Fr-2 [18,19] . More recently, potential inhibitors were isolated from Aster tataricuswhich exhibited antiinflammatory effects bypreventing the downstream activation of the mitogen-activated protein kinase signaling pathway [20,21] . A. tataricus was found to protect retinal damage in diabetic rats due to the antioxidant and antiinflammatory effects [22] and attenuated neuroinflammation by decreasing the oxidative stress and inhibiting the cytokine production in LPS-stimulated rat astrocytoma cell line (C6) and THP-1 cells [23] .…”
mentioning
confidence: 99%